THE STRENGTHENING RELATIONSHIP OUTCOME STRATEGY IN RETAIL BUSINESS IN INDONESIA - Chr. Whidya Utami (Jurnal Manajemen Pemasaran, 2008)
Retail Business covers an activity that involves the sale of goods to customers for their own use rather than to shops. High competition and customers’ retention effort have motivated retailers in seeking a strategy to win the competition. The aims of this paper are: (1) how to implement relationship marketing in retail business in Indonesia, (2) how to implement strengthening relationship outcome strategy in retail business through communication, preferential treatment, personalization, and rewarding. Through communication, preferential treatment, personalization, and rewarding, it is expected to be able to create a long term and continuous relationship.